Control and agency in student–teacher relations: a cross–cultural perspective on Finnish and Korean comprehensive schools - Junghyun Yoon; Maria Rönnlund (Routledge, Taylor & Francis Group, 2022)
Drawing on a cross-cultural, qualitative study in Finnish and Korean comprehensive schools, we explore how teacher control and student agency are manifested and exercised in the teaching and learning practices of the “official school” and in the student–teacher interactions of the “informal school”. We also elaborate on how students reflect on control and agency. Bernstein’s concepts of framing and classification are employed as a theoretical lens with which to examine control, agency and hierarchy. Data consists of school observations and interviews with students aged 12 to 14 and their teachers, conducted in six schools. The findings indicate that student agency is intensively constrained in their participation in teaching-learning practices. The analysis also reveals a paradox where students do not welcome increasing their agency through student-oriented lessons. Moreover, the controlling and caring roles of teachers and the exertion and limitation of student agency appear differently in the Finnish and Korean schools studied. Students seem to desire a refined balance between control and agency while revealing conforming and self-critical attitudes towards the school system and teacher control. Finally, our analyses of control, agency and hierarchy among school members leads this article into a discussion of democratic school culture from a cross-cultural perspective.